Anterior segment configuration and retinal nerve fiber layer analysis post pediatric cataract surgery: A systematic review - Giffarinnisa, Aulia; Rahmah, Marlyanti Nur; Maharani, Ratih Natasha; Waspodo, Noro (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Cataracts are the leading cause of visual impairment and blindness worldwide.  Most children with cataracts require surgery, and only a few can be treated conservatively. Cataract surgery in pediatric patients presents distinct challenges and potential complications that differ from those encountered within the adult demographic. The surgical intervention for cataracts may markedly modify the inherent architecture of the anterior segment, thereby resulting in alterations to the thickness of the retinal nerve fiber layer (RNFL). This systematic review aims to determine the anterior segment configuration and RNFL analysis in post pediatric cataract surgery.Methods: This research is a systematic review study regarding anterior segment configuration and RNFL analysis in post-pediatric cataract surgery. The literature search used the PRISMA guidelines through PubMed, Science Direct, Cochrane, and Clinical Key, with the keywords "cataract," "anterior segment," and “RNFL thickness,” alongside “children,” and “post-surgery.” Results: There were 10 final articles identified in this systematic review that met the inclusion criteria. The article discusses the anterior segment configuration and RNFL analysis in post pediatric cataract surgery. Of the 10 articles identified, those articles found changes in the central corneal thickness and anterior chamber depth. There is also a thinning in RNFL thickness, but other studies also stated no significant differences in RNFL thickness between preoperation, one month after surgery, and standard control.Conclusions: Cataract is still a health problem, especially in children. Cataract surgery can affect both the anterior segment and RNFL thickness.